A study on the reading behaviours among users in Perpustakaan Desa zone 10 Nabawan, Sabah / Pulin Sayau - Sayau, Pulin (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2014)
This is descriptive study of reading behaviours among users in Perpustakaan Desa zone 10 Nabawan. The statically of data visiting the library is becoming important to measure the visitors and users. In this study, might examine the relationship of reading behaviours, awareness, material, activities and facilities. The sample of data collected at Perpustakaan Desa Kg Tetagas, Perpustakaan Desa Pemunterian and Perpustakaan Desa Kg Sapulut using simple random sampling , 100 users were selected from a population 32,000. The survey instrument was designed in the form of structured questionnaire. The findings highlighted some factors related to users such as users visit to the library because of library environment; peaceful place to read. The limitations on types of book provided, references books for students limited and old dated. Questionnaires are distributed to Focus Group within two weeks directly and SPSS 20.0 version is using to analyze data.